Performance of dairy heifers grazing on Urochloa decumbens pastures deferred for two periods - Teixeira, Fábio Andrade; Silva, Fabiano Ferreira da; Bonomo, Paulo; Pires, Aureliano José Vieira; Nascimento, Paulo Valter Nunes; Gonçalves Neto, João (Acta Scientiarum. Animal Sciences, 2014)
Voluntary intake and performance of dairy heifers grazing on Urochloa decumbens pastures with two deferral periods are evaluated. The totally randomized experimental design consisted of two treatments and seven replications, with two deferral periods: T1 = 95 and T2 = 140 days. Fourteen Holstein-Zebu heifers, average body weight (BW) 300 kg, were used. Intake of forage dry matter was 2.5% and 1.2 BW respectively for treatments 95 and 140 days. In treatment T2 the animals had an intake of only 139.5 g of CP, due to low nutrient content, or rather, 3.4% of CP in the forage available. There was an intake of NDF of 1.7% and 1.0 of BW for T1 and T2, respectively. The average daily weight gain was 785.8 g day-1 for T1 and average weight loss of -31.1 g day-1 for T2. Deferral of pastures Urochloa decumbens for 95 days to allow a 1.5 lodging index provides greater consumption and performance of dairy heifers. Deferral of Urochloa decumbens pastures to allow a 1.5 lodging index provides greater intake and performance of dairy heifers.